Implementasi Pelayanan Publik Birokrasi Di Indonesia - Fahlevi, Muhammad Reza; Nuriah, Asma; Sinurat, Try Auliana; Sitanggang, Anggreni Tioda; Purba, Friskilawati; Pakpahan, Yezkyna R; Silaen, Theresya N.E; Ivanna, Julia (Mahesa Research Center, 2023)
The implementation of public policies is something important. Public policies that are made will only become 'paper tigers' if they are not successfully implemented. Therefore, the implementation of public policies needs to be done by considering various factors, so that the intended public policies can actually function as a tool to realize the desired expectations. In other words, the implementation of public policy is an effort to realize a decision or agreement that has been previously determined. In the early 1970s, implementation was seen as something that was not problematic in terms of policy, because it was assumed that after a policy was taken, it needed to be carried out just like that. This view has begun to change since the publication of Pressman and Wildavsky's study entitled Implementation in 1973. They examined federal government programs for unemployed inner-city residents of Oakland, California, the results of these studies showed that programs job creation has not been implemented in the manner anticipated by policy makers. Other studies have also confirmed that Great Society programs implemented by the Johson administration (1963-1968) in the United States did not achieve their desired goals and that the problem was in the way the program was implemented. Research in other countries as well, such as in England in the early 1970s found the same evidence, that the government was not successful in realizing policies aimed at bringing about social reform. The issue of public policy implementation has attracted the attention of social science experts, particularly political science and public administration, both in developed and developing countries.